Испытания вагона-платформы универсальной - Сенько, Вениамин Иванович; Макеев, Сергей Валерьевич; Чепурной, Анатолий Данилович; Шейченко, Роман Игоревич; Литвиненко, Александр Витальевич; Граборов, Роман Викторович; Ткачук, Николай Анатольевич; Чубань, Марина Александровна (Национальный технический университет "Харьковский политехнический институт", 2016)
В статье описаны три вида испытаний (испытание на статическую прочность, на прочность при соударении, расчетно-экспериментальная оценка сопротивления усталости конструкции), включенных в объем предварительных испытаний опытного образца вагона-платформы универсального. По результатам испытаний сделано заключение, что напряжения в несущих элементах конструкции вагона при квазистатических нагружениях и при соударениях, а также показатели сопротивления усталости конструкции вагона соответствуют требованиям конструкторской документации, технического задания и нормативных документов.

The article contains the analysis of the experience and the results of the test center of rail car-building products. It describes methodology and analysis of results of the tests (static strength, strength at the collision, calculated and experimental evaluation of the fatigue resistance of the structure of the rail car), included in the scope of preliminary tests of the prototype of the universal platform car, model 13-9990-01. The main objective of the static strength testing was to evaluate the strength, the bearing capacity of the structure of the car. Test for strength in the collision was carried out for experimental test of design strength and stability of the rail car at the specified test modes of the collision. Registration of strain in structural elements of the rail car was performed using strain gauges. Obtained allocations of stress on the elements of the rail car are presented and evaluated. During the third type of preliminary tests the verification of compliance with norms of the reserve fatigue resistance of the structure was carried out. According to the results of tests the conclusion about conformity of rail car to requirements of the car design documentation, technical specifications and regulations was made. It was concluded that the maximum stress in the structural elements of the rail car under the quasi-static load and in the collisions, as well as indicators of fatigue resistance of the structure of the rail car are within permitted. Obtained results serve for future comparison with the data of numerical analysis by the finite element method.
Testing of the universal platform car
Keywords: статическая прочность; прочность при соударении; сопротивление усталости конструкции; static strength; strength in the collision